Literature Review : Terapi Menulis Terhadap Kecemasan Korban Bullying di Indonesia - Cempaka, Anindya Arum (JURNAL NERS LENTERA, 2022)
Introduction: Bullying has significantly affected victims for a long time. The effect of bullying on victims is anxiety. Victims will also show lower levels of self-esteem and self-efficacy. If not handled, feelings of anxiety experienced by victims can increase the risk of depression and suicide. One therapy that can be used to overcome psychological problems in victims of bullying is to use writing therapy. Writing therapy can improve individual understanding in dealing with stress, anger, anxiety, and depression. Methods: The strategy of searching for research articles relevant to this research topic was carried out using the keywords: “writing therapy”, “anxiety”, “victims of bullying”, and “Indonesia”, to several major databases such as PROQUEST, EBSCO and GOOGLE SCHOLAR, with limitations time is from January 2013 to July 2022. Research articles are reviewed and selected according to the sample inclusion criteria. At the beginning of the search, 1117 articles were found relevant to the topic, but only 6 articles met the inclusion criteria. After that, the researcher assessed the 6 articles with Duffy's Research Appraisal Checklist Approach. Results: The results of 5 studies showed that writing therapy effectively reduced anxiety levels in victims of bullying in their teens and adults. Meanwhile, in research with respondents aged children, writing therapy is ineffective in reducing anxiety levels. Conclusion: Writing therapy effectively reduces anxiety levels in adolescent and adult respondents.